Erector spinae plane block for rescue analgesia following caesarean delivery - Elkoundi, Abdelghafour; Zemmouri, Adil; Najout, Hamza; Bensghir, Mustapha (Anestezjologia Intensywna Terapia, 2021)
Pain after caesarean section is still a common and important source of patient dissatisfaction in many obstetric centres. With intrathecal morphine combined with multimodal analgesia, approximately 5–10% of patients experience severe breakthrough pain after caesarean delivery that is difficult to manage [1]. Planned erector spinae plane (ESP) block can result in excellent postoperative analgesia associated with high patient satisfaction after caesarean delivery [2, 3]. However, the role of this block for rescue analgesia following caesarean section has never been described. We present a case in which bilateral ESP block was used as rescue analgesia in a woman who had severe postoperative pain following elective caesarean delivery under spinal anaesthesia combined with multimodal analgesia. The patient described in this case gave written consent for publication of this observation.